Inhaled Albuterol Use and Impaired Lactate Clearance in Patients With Sepsis: A Retrospective Cohort Study. (March 2021) - Maeda, Tetsuro; Paralkar, Janvi; Kuno, Toshiki; Patrawalla, Paru
Background: Lactate clearance has become important in the management of sepsis. However, factors unrelated to sepsis-induced hyperlactatemia, including β-2 adrenergic agonists, can interfere with lactate clearance. Objectives: To investigate the association of inhaled albuterol with lactate clearance in patients with sepsis. Methods: This was a single-center retrospective cohort study. Adult patients with sepsis diagnosed in the emergency department from May 2015 to May 2016 with initial lactate levels >2 mmol/L and serial lactate measurements 2 to 6 hours apart were included. Patients were divided into 2 groups based on whether they received inhaled albuterol between lactate measurements. The primary end point was lactate clearance of 10%. Secondary end points included intensive care unit (ICU) consultation and in-hospital mortality. A multivariate logistic regression analysis was performed to assess the effect of inhaled albuterol on lactate clearance. Results: Of 269 patients included, 58 (22%) received inhaled albuterol between lactate measurements. This group had a significantly higher prevalence of pulmonary disease and a lower initial lactate compared to those who did not receive inhaled albuterol. They had a significantly lower rate of lactate clearance (45% vs 77%, P < .001); however, ICU consultation (71% vs 57%, P = .066) and in-hospital mortality (19% vs 22%, P = .64) were not significantly different. A multivariate logistic regression analysis adjusting for age, sex, chronic kidney disease, cirrhosis, cancer, septic shock or severe sepsis, and the amount of intravenous fluids received showed that inhaled albuterol was independently associated with impaired lactate clearance (adjusted odds ratio: 0.26, 95% confidence interval: 0.14-0.50, P < .001). Conclusions: Inhaled albuterol in patients with sepsis was associated with impaired lactate clearance without an increase in ICU consultation or in-hospital mortality. Impaired lactate clearance in patients with sepsis who receive inhaled albuterol should be interpreted with caution.